Implementación de un sistema de información para la planeación de intendencia en la incorporación de soldados que prestan el servicio militar. (2014)
The present work aims to design an information system for the Directorate of Administration of the Colombian National Army, in order to respond constant processing requirements necessary for planning the timely supply of war material.